Climate change economics : why international accords fail - Van Kooten, G. C. (Cheltenham, UK ; Northhampton, MA : Edward Elgar, 2004)
This book examines the economic case for policy to mitigate climate change, and to investigate the types of policies that should be implemented if any.It is a seriously flawed agreement and as such does not offer much hope in terms of the international communiy's ability to find a policy` prescription that might slow or even prevent anthropogenic emissions of so called greenhouse gasses from rising in the future.
Includes bibliographical references (p. 152-163) and index.
aia 24/09/13
Loans
Keywords: Climatic changes; Climatic changes; Environmental policy